A new species of Schaefferia Absolon (Collembola: Hypogastruridae) from Chukotka, Russia, with remarks on the related forms - Babenko, Anatoly (Zootaxa, 2019)
A new species of the genus Schaefferia, S. bermani sp. nov., is described from the eastern coast of Chukchi Peninsula (Russia). It is most similar to S. czernovi (Martynova) which is widespread in the northern parts of more western regions of the Palaearctic. Both species are characterised by the presence of 5+5 ocelli and a similarly shortened furca, but differ in morphology of the labial palp and chaetotaxy of Abd.4. Remarks on several related forms, including Japanese S. quinqueoculata (Yosii), are given.